Sur la controlabilité exacte de l’equation des plaques vibrantes - Niane, Mary Teuw; Sene, Abdoulaye (Revista Matemática Complutense, 2002)
We define, for the trace of solution of vibrating plates equation, norms with initial conditions in no regular spaces. Then, we give the corresponding exact controllability results.